Evidence-Based Practice: Challenging the Rational Wisdom. Issue 9 (29th July 2017) - Hall, Jeremy L.
ABSTRACT: The field of performance measurement (PM) is firmly entrenched as a management practice in many governments, agencies, and nonprofit organizations. Though emerging later, the field of evidence-based practice (EBP) has developed simultaneously as a new approach to enhance agency performance. While both rationality-oriented reforms intend to enhance program or agency performance, these two related rational approaches are seldom considered in concert. This essay examines the conceptual underpinnings and practical linkages between PM and EBP to explore how EBP and PM can be jointly implemented as tools to advance agency goals. As rational approaches aimed at improving performance, these two distinct tools are not substitutes, but integrated components of a results-driven strategic management approach. As a conceptual assessment, the article offers practical advice and broad appeal to performance-oriented practitioners seeking to improve agency performance.